Quality Analysis and Prediction for Start-up Process of Injection Molding Processes. Issue 18 (2018) - Zou, Mingjun; Zhao, Luping; Wang, Shu; Chang, Yuqing; Wang, Fuli
Abstract: As a typical batch process, injection molding process plays an important role in industry. This work focuses on the start-up process of injection molding process. Based on a deep study of the start-up process of injection molding process, a phase-shift sliding window modelling scheme is proposed in this paper for quality prediction. Firstly, to deal with the time-varying problem during the start-up process, sliding windows are built in the batch direction, and multiple continuous models are established to capture the relationship between the process variables and the quality respectively. Secondly, according to the operational characteristics of the plastication phase of injection molding process, a hypothesis that the plastication phase of the current batch has a greater impact on the quality of the next batch than the quality of the current batch is proposed, and the existence of this assumption is verified by the simulation with experimental data. Under the premise of the above assumptions, a new quality prediction scheme is proposed and is verified to be more accurate than the traditional methods.